Emerging Digital Spaces: The Case of Bluesky’s Rise During 2024 Brazilian Elections - Buzelin, Arthur; Bento, Pedro; Aquino, Yan; Chagas, Arthur; Dutenhefner, Pedro Robles; Malaquias, Samira; Estanislau, Victoria; Santana, Caio; Dayrell, Lucas; Mesquita, Lucas; Locatelli, Marcelo Sartori; Pappa, Gisele; et al. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2025)
This paper examines political discourse on Bluesky during Brazil’s 2024 municipal elections, following the unexpected Twitter ban in the country. Using keyword-based data collection and embedding-based sentiment analysis (WEAT), we analyze user perceptions and their evolution across electoral phases. Our findings reveal significant shifts in candidate popularity, closely tied to electoral outcomes and broader ideological trends, with clear patterns of polarization. Notably, candidate sentiment fluctuated between election rounds, reflecting both victories and defeats. This study highlights Bluesky’s emerging role in digital political engagement when mainstream platforms are disrupted.